PENGARUH PENGEMBANGAN KARIER TERHADAP PENINGKATAN KINERJA PEGAWAI PADA KANTOR PT PLN (PERSERO) UNIT PENGATUR BEBAN SULSELRABAR MAKASSAR - Guntur Suryo Putro; Arfiany Sahban (COMPETITIVENESS, 2019)
PT PLN (Persero) in terms of career planning strategy allows the organization to develop and place its employees in a position that suits their interests, needs and career goals. PT PLN (Persero) in the management of human resources career is very attentive to the career development of its employees. the research was carried out at the office of PT PLN (Persero) Sulselrabar Load Management Unit, Jln Letjend Hertasning Makassar. the sample taken in this study was 55 people. From the calculation of regression coefficients obtained that the influence of career development variables have a significant effect on the performance of employees at the Office of PT PLN (persero) Makassar Sulselrabar Load Management Unit. The regression equation is as follows: Y= 0.969+ 0.604 X. T calculated value obtained and significant level on the table of 0.000 which means 0.0000.05 then Ho rejected and Ha received means that career development can affect the performance of employees in the office of PT PLN (Persero) Makassar Sulselrabar Load Management Unit at the standard level of its coefficient of 0.730 or 73%.                                                                                                                                                                Keywords: Development, Career, Performance, PLN